Modes of incorporation: a conceptual and empirical critique. Issue 1 (2nd January 2016) - Waldinger, Roger; Catron, Peter
ABSTRACT: Entering the debate over segmented assimilation, this paper seeks to refocus discussion on a core, but neglected claim: that inter-group disparities among immigrant offspring derive from differences in a contextual feature shared by immigrant and immigrant descendants: a nationality's mode of incorporation. The paper engages in both theoretical and empirical assessment. We critically examine the concept of mode of incorporation, demonstrating that its operational implications have not been correctly understood; consequently, the core hypothesis has never been appropriately tested. The second part of the paper implements those tests, making use of the Children of Immigrants Longitudinal Survey. We do so by using nationality as a proxy for mode of incorporation, systematically contrasting more advantaged against less advantaged nationalities. We show: (a) that tests systematically varying modes classified as more or less advantageous yield inconsistent outcomes; (b) that positive or negative modes of incorporation are associated with few long-lasting effects; (c) that differences in governmental reception are particularly unlikely to be associated with interethnic disparities; and (d) that compared to theoretically relevant nationalities, neither Mexicans, a nationality assigned to a negative mode of incorporation, nor pre-Mariel Cubans, a nationality assigned to positive mode of incorporation, prove distinctive.